Internet of Things security framework based on near field communication with Otway Rees protocol - Musa Jaber M.; Yussof S.; Ali M.H.; Khalil Abd S.; Jassim M.M.; Alkhayyat A. (John Wiley and Sons Inc, 2023)
Cost effectiveness; Data transfer; Near field communication; Network security; Sensitive data; Communications protocols; Cost effective; Data-transmission; Floodings; Near-field communication; Network connectivity; Potential risks; Security frameworks; Sensitive datas; Transmitting data; Internet of things